Contraception choice for female endurance athletes: What's sport got to do with it? A cross-sectional survey - Ryall, S.; Ohrling, H.; Stellingwerff, T.; Black, S.; Reilly, K.; Thornton, J. S. (Sports Medicine, 2024)
Background: While there are several prescribed contraceptive methods available, limited evidence exists to guide contraceptive decision-making in the context of endurance sport. Objectives: Study objectives were to characterize current and previous use, perceived impacts, and the decision process around contraceptives in endurance athletes. Methods: This was an online survey study with female endurance athletes recruited through social media and emails to university/club coaches and sport organizations. Quantitative and qualitative data were analyzed with descriptive statistics and conventional content analysis, respectively. Results: A total of 323 female endurance athletes participated. Among current contraception users (n = 182), 51% used hormonal intrauterine devices (hIUDs), 29% oral contraceptive pills (OCPs), and 13% nonhormonal IUDs (nhIUDs). hIUD users had the highest perceived positive training (39%) and competition (29%) impacts, citing reduced menstrual bleeding and symptoms as positive side effects. OCP and nhIUD users had higher rates of perceived negative training impacts (OCPs 10%, nhIUDs 30%). For OCP users, 31% reported perceived adverse body composition outcomes and 37% reported negative mood changes. Among nhIUD users, 74% experienced heavier, more irregular menstrual bleeding. Over half of participants were unsure about the impact of their current method on performance. For contraceptive selection, 95% felt that information from physicians was important, yet 32% felt performance was inadequately considered during counseling discussion. Athletes reported less frustration with their contraception choice when counseled in the context of sport. Conclusions: This exploratory study quantifies and qualifies the lived experiences of female endurance athletes with contraception. hIUDs were the most currently used and well-tolerated contraceptives among participants. This research offers valuable insights for athletes seeking contraception and looking to optimize both performance and health, along with the healthcare professionals guiding them.